Sistema de Costos ABC y su impacto en la rentabilidad de la Empresa Zicca Calzados. - Gutierrez Poma, Zoila Elena (2012)
This research paper show the application of CBA system to propose such an option to redesign the current system into Zicca Calzados enterprise to determine the impact in the profitability of selling boots, particularly to leather boots and synthetic boots. It was applied a methodology to calculate CBA costs to precise the indirect cost in the production of leather boots and synthetic boots; a important factor in this methodology is the identification of the driver cost, called also inductor cost. The results obtained shown that exist a difference in the indirect cost in the manufacturation of leather boots and synthetic boots; in fact, the difference between CBA method and traditional method for leather boots was of -1.64%, it means that really has less profitability that traditional method may calculate. In case of synthetic boots the difference was 0.85%, it means that really has more profitability that traditional method may calculate. The results obtained let the company have a much clearer scenario to make better decisions with more accurate information as it relates to strategy, operational policy and price fixation.